The Olive: fruit of gods - De La Fuente de Diez Canseco, Luciana (2017)
The new concept of sustainable development satisfies the needs of the present without compromising the capacity of future generations to satisfy theirs. In order to achieve the proposed goals, it is essential to harmonize and interconnect three core elements: economic growth, social inclusion and environmental protection for the generations of both today and tomorrow.